Neurovascular Dysregulation During Exercise in Type 2 Diabetes - Grotle, Ann-Katrin; Kaur, Jasdeep; Stone, Audrey J.; Fadel, Paul J. (Frontiers in Physiology, 2021)
Emerging evidence suggests that type 2 diabetes (T2D) may impair the ability to properly adjust the circulation during exercise with augmented blood pressure (BP) and an attenuated contracting skeletal muscle blood flow (BF) response being reported. This review provides a brief overview of the current understanding of these altered exercise responses in T2D and the potential underlying mechanisms, with an emphasis on the sympathetic nervous system and its regulation during exercise. The research presented support augmented sympathetic activation, heightened BP, reduced skeletal muscle BF, and impairment in the ability to attenuate sympathetically mediated vasoconstriction (i.e., functional sympatholysis) as potential drivers of neurovascular dysregulation during exercise in T2D. Furthermore, emerging evidence supporting a contribution of the exercise pressor reflex and central command is discussed along with proposed future directions for studies in this important area of research.